TREE ONION A LITTLE PART IN GLOBAL BIODIVERSITY - V. A. Kokoreva (Овощи России, 2017)
Only administrative measures are not able to ensure the priority of existence for great number of biological species. There should be contribution of each population, regions in many countries and each person. Responsibility for nature and concern for future generation are our common duty. The forgotten culture of tree onion has revived as it has been shown in Italy and the work for preservation of its biodiversity is in progress, already showing fruitful results. The interesting cuisine recipes with tree onion are also presented in the article.